Bionic extracellular matrix hydrogel hydrogel with adjustable hardness and viscoelasticity and preparation method thereof
By constructing hydrogels of different compositions and using the interpenetrating network of GelMA and sodium alginate, the hardness and viscoelasticity of extracellular matrix hydrogels are adjusted, solving the problem that the existing technology is difficult to regulate the physical characteristics of extracellular matrix, and providing an effective platform for studying cell biological effects.
Patent Information
- Application Number
- CN202411694043.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to provide a hydrogel cell culture platform that can regulate the hardness and viscoelastic properties of extracellular matrix, which is used to study cell biological effects and regulatory mechanisms.
By mixing methacrylated gelatin (GelMA) with different amino substitution degrees with sodium alginate of different molecular weights and cross-linking reactions in UV and calcium chloride solutions, a bionic extracellular matrix hydrogel with adjustable viscoelasticity and hardness was constructed.
The flexible regulation of viscoelasticity and hardness of hydrogels is achieved, providing an ideal research platform for studying the cell's response to matrix hardness and viscoelasticity, thereby providing an in-depth understanding of the pathogenesis of the disease.
Smart Images

Figure CN119505288A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedicine, and in particular to a bionic extracellular matrix hydrogel with adjustable hardness and viscoelasticity and a preparation method thereof. Background Art
[0002] Viscoelasticity refers to the property of a material that exhibits both viscous and elastic behavior under stress. A material with viscoelasticity will produce both instantaneous elastic deformation and time-dependent viscous flow when subjected to stress. In layman's terms, the mechanical response of a viscoelastic material is both as fast as a spring (elasticity) to return to its original shape and as slow as honey (viscosity) to flow.
[0003] Many biological tissues exhibit viscoelastic properties. In some diseases, the viscoelastic characteristics of tissues change. For example, non-alcoholic hepatitis (NASH) can lead to an increase in the viscoelasticity of liver tissues. This abnormality in tissue viscoelasticity can induce liver cell carcinogenesis. Therefore, understanding the biological effects of extracellular viscoelasticity changes on cells is important for understanding the pathogenesis of diseases.
[0004] Extracellular matrix stiffness refers to the ability of the extracellular matrix to deform when subjected to external forces. For example, the extracellular matrix of bone tissue contains a large amount of collagen fibers and minerals. The deposition of minerals makes the bone tissue very hard and has an extremely high elastic modulus. In contrast, the ECM of brain tissue is very soft and has almost no fibrous extracellular matrix components. It is mainly composed of some proteoglycans, matrix proteins and water.
[0005] Differences in the hardness of the extracellular matrix play an important role in determining cell fate. Studies have shown that softer matrices (similar to brain tissue) help stem cells differentiate into neurons, while harder matrices (similar to bone tissue) are more likely to induce them to differentiate into osteoblasts. Therefore, the hardness of the ECM is one of the important signals in the cell microenvironment that guide cell differentiation. In addition, under pathological conditions, disorders in the hardness of the extracellular matrix caused by excessive formation or degradation of the extracellular matrix can also affect the course of disease development. For example, under pathological conditions such as tumors, the hardness of the ECM often changes, and the ECM in tumor tissues is often harder than normal tissues. This increase in hardness can promote tumor progression by affecting the migration and invasion ability of tumor cells.
[0006] In order to understand the biological effects of physical properties such as extracellular matrix hardness and viscoelasticity on cells and their regulatory mechanisms, a hydrogel cell culture platform with adjustable hardness and viscoelasticity is needed. Summary of the invention
[0007] In order to solve the above technical problems, the first purpose of the present invention is to provide a biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity. It has good biocompatibility and becomes an ideal platform for studying the effects of matrix viscoelasticity or hardness on cell biology. The second purpose is to provide a preparation method thereof.
[0008] To achieve the first objective, the present invention is implemented by the following technical scheme: a method for preparing a bionic extracellular matrix hydrogel with adjustable hardness and viscoelasticity, characterized in that the preparation is carried out according to the following steps:
[0009] (1) Weighing freeze-dried GelMA hydrogels with different amino substitution degrees, adding them into a phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution to dissolve them, and obtaining a GelMA solution;
[0010] (2) Weighing sodium alginate hydrogels of different molecular weights, adding pure water to dissolve them, and preparing sodium alginate solutions;
[0011] (3) mixing the GelMA hydrogel solutions with different amino substitution degrees in step (1) and step (2) with the sodium alginate hydrogel solutions with different molecular weights, and performing a first cross-linking reaction under ultraviolet light;
[0012] (4) subjecting the ultraviolet-irradiated hydrogel to an ionic crosslinking reaction in a calcium chloride solution to obtain a product.
[0013] In the above scheme: in step (1), the concentration of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution is 0.025%-0.05% (w / v).
[0014] In the above scheme: in step (1), the dissolution condition is to heat and dissolve in a water bath at 60-70°C in the dark for 20-30 minutes, with shaking several times during the process.
[0015] In the above scheme: in step (2), sodium alginate is dissolved by stirring at room temperature.
[0016] In the above scheme: the amino substitution degree of the GelMA is 60%-90%, and the molecular weight of the sodium alginate is 50K-300K.
[0017] In the above scheme: the wavelength of ultraviolet light is 405nm, and the light intensity is 25mW / cm 2 .
[0018] In the above scheme: the concentration of calcium ions in the calcium chloride solution is 5-20 mM.
[0019] The present invention realizes the regulation of hydrogel viscoelasticity by controlling the molecular weight of sodium alginate in the hydrogel system and the ratio of covalent bonds of irreversible crosslinking. By constructing an interpenetrating network hydrogel of methacryloylated gelatin (GelMA) and sodium alginate, it is possible to achieve regulation of viscoelasticity without changing the above other parameters, and has good biocompatibility. Specifically, when high molecular weight sodium alginate has a long molecular chain, more crosslinking points can be formed on each molecular chain when calcium ions are crosslinked. Calcium ions interact with the carboxyl groups (mannuronic acid units in the G region) in sodium alginate to form an "egg box" structure. This structure connects multiple molecular chains to form a relatively tight and uniform three-dimensional network. Therefore, high molecular weight sodium alginate can form a denser and more uniform crosslinking network, showing stronger elasticity and lower viscosity. The chain segments of low molecular weight sodium alginate are shorter, and relatively few crosslinking points can be formed. This will cause the crosslinking network to be not dense enough, and the interaction between the molecular chains is weak, so its viscous component is more prominent and the elasticity is weak. The cross-linked network has larger voids, making it more viscous rather than elastic.
[0020] GelMA is a chemically modified gelatin derivative widely used in the fields of tissue engineering, biomedical engineering, etc. It retains the biocompatibility and degradability of gelatin, and at the same time increases the photocrosslinking performance through methacryloyl modification, so that it can be quickly cured under ultraviolet or visible light irradiation to form a hydrogel with a three-dimensional structure. By adjusting the reaction conditions to change the degree of introduction of methacryloyl groups into the gelatin molecules, the degree of substitution of GelMA can be changed, so that GelMA can form more covalent crosslinks after photocrosslinking. In order to maximize the difference in viscoelasticity, we use GelMA with high and low amino substitution degrees to mix with high and low molecular weight sodium alginate hydrogels, respectively, to form interpenetrating network hydrogels with low viscoelasticity and high viscoelasticity. The raw materials of the present invention are easy to obtain and the operation is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a graph showing the shear modulus, storage modulus (G'), loss modulus (G"), creep effect, elastic modulus, and pore structure of the hydrogels prepared in Examples 1 and 2.
[0022] Figure 2 The graphs show the shear modulus, storage modulus (G'), loss modulus (G"), creep effect, elastic modulus, and pore structure results of the hydrogel of Example 3.
[0023] Figure 3 This is a graph showing the test results of the hydrogel shear modulus, storage modulus (G'), loss modulus (G"), and elastic modulus of Example 4.
[0024] Figure 4This is a graph showing the test results of shear modulus, storage modulus (G'), loss modulus (G"), and elastic modulus of the hydrogel of Example 5.
[0025] Figure 5 This is a graph showing the test results of shear modulus, storage modulus (G'), loss modulus (G"), and elastic modulus for the hydrogel of Example 6. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0027] Example 1
[0028] 1. Preparation of GelMA hydrogel:
[0029] Weigh 90% amino-substituted lyophilized GelMA, dissolve it in 0.025% (w / v) phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution, heat and dissolve it in a water bath at 60-70°C in the dark for 20-30 minutes, shake several times during the process, and prepare a GelMA solution (concentration 10% w / v);
[0030] 2. Preparation of sodium alginate hydrogel:
[0031] Sodium alginate hydrogel powder with a molecular weight of 300K (high molecular weight) was dissolved in pure water at room temperature with stirring for 6 hours to prepare a sodium alginate solution with a concentration of 0.5% (w / v).
[0032] 3. The prepared GelMA solution with 90% amino substitution degree and 300K sodium alginate solution were mixed in a volume ratio of 1:1, and the obtained mixed hydrogel was a low-viscoelastic hydrogel (the final concentration of GelMA was 5% w / v, and the final concentration of 300K sodium alginate was 0.25%). This was the Slow group.
[0033] 4. Gelation process of hydrogel solution
[0034] The hydrogel was exposed to ultraviolet light (light wavelength: 405 nm; light intensity: 25 mW / cm 2 ) for 30 seconds to perform the first photocrosslinking; then the hydrogel was ionically crosslinked in a calcium chloride solution with a calcium ion concentration of 20 mM.
[0035] Example 2
[0036] 1. Preparation of GelMA hydrogel:
[0037] Weigh 60% amino-substituted lyophilized GelMA, dissolve it in 0.025% (w / v) phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution, heat and dissolve it in a water bath at 60-70°C in the dark for 20-30 minutes, shake several times during the process, and prepare a GelMA solution (concentration 10% w / v);
[0038] 2. Preparation of sodium alginate hydrogel:
[0039] 50K (low molecular weight) sodium alginate hydrogel powder was dissolved in pure water at room temperature with stirring for 6 hours, and the concentration of the sodium alginate solution was 2% (w / v).
[0040] 3. Configuration ratio of different viscoelastic hydrogels:
[0041] The prepared GelMA solution with 60% amino substitution degree and 50K sodium alginate solution were mixed in a volume ratio of 1:1, and the obtained mixed hydrogel was a high viscoelastic hydrogel (the final concentration of GelMA was 5% w / v, and the final concentration of 50K sodium alginate was 1%).
[0042] 4. Gelation process of hydrogel solution:
[0043] The hydrogel was exposed to ultraviolet light (light wavelength: 405 nm; light intensity: 25 mW / cm 2 ) for 30 seconds to perform the first photocrosslinking; then the hydrogel was ionically crosslinked in a calcium chloride solution with a calcium ion concentration of 20 mM. The obtained group is the Fast group.
[0044] The shear modulus, storage modulus (G'), loss modulus (G"), creep effect, elastic modulus, and pore structure of the hydrogels prepared in Examples 1 and 2 were tested. Since high viscoelastic hydrogels have the characteristic of faster stress relaxation rate, the experimental results in this part are referred to as Fast group for high viscoelastic hydrogels and Slow group for low viscoelastic hydrogels.
[0045] Figure 1 Figure A: When shear force is applied to the hydrogel, it takes 100-120 seconds for the shear modulus of the Fast group hydrogel to be reduced to half of the initial shear modulus, while it takes 3000-4000 seconds for the Slow group, indicating that the two hydrogels have strong differences in viscoelasticity.
[0046] Figure B: The storage modulus (G') and loss modulus (G") of the two groups of hydrogels were detected. The loss modulus of the hydrogel in the Fast group was significantly higher than that in the Slow group, indicating that the hydrogel in the Fast group had higher viscosity.
[0047] Figure C: The creep effect of the two groups of hydrogels was detected. Under constant stress, the strain of the Fast group of hydrogels gradually increased, and the reaction material had viscoelastic characteristics.
[0048] Figure D: After the two groups of hydrogels were gelled, they were immersed in PBS for 1 day respectively. After 7 days, it was detected that the two groups of hydrogels had similar elastic moduli.
[0049] Figure E: Scanning electron microscopy was used to observe the pore structures of the two groups of hydrogels, and it was found that the two groups of hydrogels had similar pore sizes.
[0050] Example 3
[0051] According to the methods of Examples 1 and 2, GM60 and GM90 were used respectively, and mixed with sodium alginate with a molecular weight of 50K, so that the final concentration of GelMA was 5% (w / v) and the final concentration of sodium alginate was 1% (w / v). Two groups of hydrogels were obtained, namely GM60+50K and GM90+50K. Since GM90 can form more covalent cross-links during the photocross-linking process, the viscoelasticity is reduced.
[0052] The shear modulus, storage modulus (G'), loss modulus (G"), and elastic modulus of the hydrogel of Example 3 were tested.
[0053] Figure 2 Middle, Figure A: When shear force is applied to the hydrogel, it takes 90-120 seconds for the shear modulus of the hydrogel in the GM60+50K group to be reduced to half of the initial shear modulus, while it takes 250-310 seconds for the GM90+50K group, and the viscoelasticity is reduced.
[0054] Figure B: After the two groups of hydrogels were gelled, they were immersed in PBS for 1 day respectively. The elastic moduli of the two groups of hydrogels were detected to be 6kPa and 8kPa respectively.
[0055] Figure C: The storage modulus (G') and loss modulus (G") of the two groups of hydrogels were detected. The GM90+50K group of hydrogels had a higher storage modulus and a lower loss modulus.
[0056] Example 4
[0057] Sodium alginate with different molecular weights was used to keep the degree of substitution, mass volume ratio and calcium chloride concentration of GelMA consistent.
[0058] The other steps were the same as in Examples 1 and 2, except that GM60 was used and mixed with sodium alginate with molecular weights of 50K and 300K, respectively, so that the final concentration of GelMA was 5% (w / v), and the final concentration of sodium alginate with low molecular weight (50K) and high molecular weight (300K) was 1% (w / v), and two groups of hydrogels, GM60+50K and GM60+300K, were obtained. Sodium alginate with high molecular weight resulted in reduced viscoelasticity of the hydrogel.
[0059] The shear modulus, storage modulus (G'), loss modulus (G"), and elastic modulus of the hydrogel of Example 4 were tested. Figure 3 shown.
[0060] Figure A: When shear force is applied to the hydrogel, it takes 120-140 seconds for the shear modulus of the hydrogel in the GM60+50K group to be reduced to half of the initial shear modulus, while it takes 1800-2000 seconds for the GM60+300K group, and the viscoelasticity is significantly reduced.
[0061] Figure B: After the two groups of hydrogels were gelled, they were immersed in PBS for 1 day respectively. The elastic moduli of the two groups of hydrogels were detected to be 6kPa and 20kPa respectively.
[0062] Figure C: The storage modulus (G') and loss modulus (G") of the two groups of hydrogels were detected. The GM60+300K group of hydrogels had a higher storage modulus and a lower loss modulus.
[0063] Example 5
[0064] The mass volume ratio of sodium alginate was changed to maintain the degree of substitution of GelMA, the molecular weight of sodium alginate and the concentration of calcium chloride consistent.
[0065] According to the method of Example 1 or 2, GM60 was used and mixed with sodium alginate with a molecular weight of 50K, so that the final concentration of GelMA was 5% (w / v), and the final concentration of sodium alginate was 1% and 0.5% (w / v), respectively. Two groups of hydrogels were obtained, namely GM60+50K (1%) and GM60+50K (0.5%). The reduction of sodium alginate concentration resulted in a decrease in the viscoelasticity of the hydrogel.
[0066] The shear modulus, storage modulus (G'), loss modulus (G"), and elastic modulus of the hydrogel of Example 5 were tested. Figure 4 As shown:
[0067] Figure A: When shear force is applied to the hydrogel, it takes 100-130 seconds for the shear modulus of the hydrogel in the GM60+50K (1%) group to be reduced to half of the initial shear modulus, while it takes 250-300 seconds for the GM60+50K (0.5%) group, and the viscoelasticity is significantly reduced.
[0068] Figure B: After the two groups of hydrogels were gelled, they were immersed in PBS for 1 day respectively. The elastic moduli of the two groups of hydrogels were detected to be 7kPa and 4kPa respectively.
[0069] Figure C: The storage modulus (G') and loss modulus (G") of the two groups of hydrogels were detected. The GM60+50K (0.5%) group of hydrogels had lower storage modulus and loss modulus. Scanning electron microscopy was used to observe the pore structure of the two groups of hydrogels, and it was found that the two groups of hydrogels had similar pore sizes.
[0070] Example 6
[0071] By changing the concentration of calcium chloride during the ionic cross-linking process, the degree of substitution of GelMA and the molecular weight and mass-to-volume ratio of sodium alginate were kept consistent.
[0072] According to the method of Examples 1 and 2, GM60 (GelMA with an amino substitution degree of 60%, the same as above) was mixed with sodium alginate with a molecular weight of 50K to make the final concentration of GelMA 5% (w / v) and the final concentration of sodium alginate 1%, and finally ion crosslinked with 5mM and 20mM calcium chloride solutions, respectively. Two groups of hydrogels, 50K+5mM and 50K+20mM, were obtained. The decrease in calcium chloride concentration resulted in a decrease in the viscoelasticity of the hydrogel.
[0073] The shear modulus, storage modulus (G'), loss modulus (G"), and elastic modulus of the hydrogel of Example 6 were tested. Figure 5 As shown:
[0074] Figure A: When shear force is applied to the hydrogel, it takes 80-110 seconds for the shear modulus of the hydrogel in the 50K+20mM group to be reduced to half of the initial shear modulus, while it takes 600-800 seconds for the 50K+5mM group, and the viscoelasticity is significantly reduced.
[0075] Figure B: After the two groups of hydrogels were gelled, they were immersed in PBS for 1 day respectively. The elastic moduli of the two groups of hydrogels were detected to be 7kPa and 4kPa respectively.
[0076] Figure C: The storage modulus (G') and loss modulus (G") of the two groups of hydrogels were detected. The 50K+5mM group of hydrogels had lower storage modulus and loss modulus.
[0077] The present invention can change the viscoelasticity and elasticity of the hydrogel by adjusting the amino substitution degree of GelMA, the molecular weight of sodium alginate, the concentration of calcium chloride, and the mass volume ratio of sodium alginate, without changing the density of cell adhesion sites (cell adhesion sites are mainly provided by the arginine-glycine-aspartic acid (RGD) sites on GelMA, and the final concentration of GelMA in the two hydrogels used in this project is 5% w / v, so they have the same density of adhesion sites).
[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity, characterized in that: Prepare according to the following steps: (1) Weighing freeze-dried GelMA hydrogels with different amino substitution degrees, adding them into a phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution to dissolve them, and obtaining a GelMA solution; (2) Weighing sodium alginate hydrogels of different molecular weights, adding pure water to dissolve them, and preparing sodium alginate solutions; (3) mixing the GelMA hydrogel solutions with different amino substitution degrees in step (1) and step (2) with the sodium alginate hydrogel solutions with different molecular weights, and performing a first cross-linking reaction under ultraviolet light; (4) subjecting the ultraviolet-irradiated hydrogel to an ionic crosslinking reaction in a calcium chloride solution to obtain a product.
2. The method for preparing the biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity according to claim 1, characterized in that: In step (1), the concentration of the phenyl (2,4,6-trimethylbenzoyl) lithium phosphate solution is 0.025%-0.05% (w / v).
3. The method for preparing the biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity according to claim 2, characterized in that: In step (1), the dissolution condition is to heat and dissolve in a water bath at 60-70° C. in the dark for 20-30 minutes, with shaking several times during the process.
4. A method for preparing a biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity according to any one of claims 1 to 3, characterized in that: In step (2), sodium alginate is dissolved by stirring at room temperature.
5. The method for preparing the biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity according to claim 4, characterized in that: The amino substitution degree of the GelMA is 60%-90%, and the molecular weight of the sodium alginate is 50K-300K.
6. The method for preparing the biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity according to claim 5, characterized in that: The wavelength of ultraviolet light is 405nm, and the light intensity is 25mW / cm 2 .
7. The method for preparing the biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity according to claim 6, characterized in that: The calcium ion concentration of the calcium chloride solution is 5-20 mM.
8. A biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity prepared by the method for preparing a biomimetic extracellular matrix hydrogel with adjustable hardness and viscoelasticity as claimed in any one of claims 1 to 7.
Citation Information
Cited By
Microcarrier for oral delivery of probiotic microcolonies as well as preparation method and application of microcarrier
CN120884556A